Modelling the assessment of traffic risk at level crossings of Lithuanian railways - Bureika, Gintautas; Gaidamauskas, Eduardas; Kupinas, Jonas; Bogdevičius, Marijonas; Steišūnas, Stasys (Transport, 2017)
The article discusses the problem of railway safety management and the criteria for evaluating the traffic risk described in various scientific publications. The research aims to assess the risk posed to railway infrastructure objects and to create a model for safety risk evaluation. The research on the traffic safety risk with respect to the infrastructure of the rail transport system was divided into three stages. The Plan–Do–Check–Act (PDCA) model can be used for investigating the problem of managing railway traffic safety risks in the Lithuanian railways. The main threats to railway infrastructure objects are defined, and the catalogue of technical parameters of level crossings of the Lithuanian railways is presented. The maximum allowable train speed, the intensity of railway and road traffic, as well as the size (width) and visibility of level crossings from the train driver’s cab are chosen as the main criteria for evaluating the vulnerability of a level crossing. The logistic regression method has been applied to rank and assess the safety of level crossings of the Lithuanian railways. The validity of the model developed in the present work for assessing traffic safety risks at level crossings of Lithuanian railways is about 86%. The suggested risk evaluation model is flexible and can be easily adapted for the evaluation and monitoring of safety risk of other elements pertaining to railway infrastructure. Finally, the basic conclusions and recommendations are provided.First published online: 24 Oct 2016